Students' Engagement and Perception towards Learning Arabic Vocabulary through the Total Physical Response Method (TPR) - Dimas Fikal Cahya Hakiki; Moh. Munir; Ika Rusdiana (Tarbawi : Jurnal Ilmu Pendidikan, 2025)
Vocabulary learning is a fundamental component in Arabic language acquisition and requires a teaching approach capable of helping students understand and retain vocabulary effectively. This research aimed to describe the engagement and perceptions of students regarding the use of the Total Physical Response (TPR) method in Arabic vocabulary learning in the seventh grade of Al-Muqoddasah Junior High School (SMP). The research used a qualitative approach with a case study research type that involved 32 students as participants. Data were collected through observation, semi-structured interviews, and documentation, and subsequently analyzed using Miles, Huberman, and Saldana's model. The research results indicated that the majority of students stated that the TPR method helped them understand and remember vocabulary more easily. Students appeared active in following instructions, showed high focus, and responded to movements with enthusiasm. The interviews revealed that students viewed movement-based learning as more enjoyable, less boring, and as enhancing their learning motivation. Although there were technical constraints such as limited classroom space, these obstacles did not affect the students' positive perceptions of the TPR method. This research concluded that using the TPR method was capable of increasing student engagement and building positive perceptions in Arabic vocabulary learning, and provides recommendations for integrating this method more systematically into learning at the junior high school level.